2021
DOI: 10.1371/journal.ppat.1009363
|View full text |Cite
|
Sign up to set email alerts
|

Innate immune signatures to a partially-efficacious HIV vaccine predict correlates of HIV-1 infection risk

Abstract: The pox-protein regimen tested in the RV144 trial is the only vaccine strategy demonstrated to prevent HIV-1 infection. Subsequent analyses identified antibody and cellular immune responses as correlates of risk (CoRs) for HIV infection. Early predictors of these CoRs could provide insight into vaccine-induced protection and guide efforts to enhance vaccine efficacy. Using specimens from a phase 1b trial of the RV144 regimen in HIV-1-uninfected South Africans (HVTN 097), we profiled innate responses to the fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(41 citation statements)
references
References 69 publications
8
33
0
Order By: Relevance
“…Identification of a robust signature of cytokine induction leading to successful vaccination would be important for further vaccine development and optimization (Arunachalam et al, 2020;Fourati et al, 2019;Hagan and Pulendran, 2018;Kuri-Cervantes et al, 2016). Immune signatures in vaccine recipients receiving yellow fever, HIV-Ade5, or HIV canary pox virus vaccine (ALVAC) vaccines have been described (Andersen-Nissen et al, 2021;Gaucher et al, 2008;Querec et al, 2009;Zak et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Identification of a robust signature of cytokine induction leading to successful vaccination would be important for further vaccine development and optimization (Arunachalam et al, 2020;Fourati et al, 2019;Hagan and Pulendran, 2018;Kuri-Cervantes et al, 2016). Immune signatures in vaccine recipients receiving yellow fever, HIV-Ade5, or HIV canary pox virus vaccine (ALVAC) vaccines have been described (Andersen-Nissen et al, 2021;Gaucher et al, 2008;Querec et al, 2009;Zak et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, although we did not determine serum cytokine concentrations, the observed changes in blood leukocyte composition are most likely not due to high concentrations of vaccination-induced inflammatory cytokines (e.g., IL-1β, IL-6, TNF). The effects reported in the racehorses may be due to a low level induction of cytokines, chemokines and other mediators, as observed after vaccination of humans against influenza [30] and more recently when analyzing the innate immune transcriptional signatures of peripheral blood mononuclear cells (PBMC) one day after vaccination of humans [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of the elicited antibodies also found that ADCC by NK cells was a major correlate of protection in the monkeys. More recent studies investigating the correlates of protection in a phase 1B trial attempting to replicate the RV144 regimen in South Africa (HVTN 097) found that innate immune pathways were highly upregulated, including signatures of ADCC and ADCP however it failed to demonstrate significant protection ( 53 ). Collectively, these findings suggest antibodies capable of driving Fc-mediated effector functions may hold promise in future interventions designed to prevent HIV transmission.…”
Section: Contribution Of Fc-mediated Effector Functions In Hiv Prevention and Viral Clearancementioning
confidence: 99%